Avaliação institucional na Universidade Federal do Ceará: a construção do Projeto Pedagógico do Curso de Agronomia sob o marco legal do SINAES - Leite, Manoel Irlano Barbosa (2017)
In this dissertation a study on the contributions in Brazil Superior Education Evaluation National System (SINAES) in the curricular area Agronomy course of the Federal University of Ceará. Thus, this research aimed to evaluate the principles and criteria that served as conceptual and political background to the construction of the pedagogical project of the Agronomy course under the SINAES framework. In addition, an external evaluation was also considered in the study, carried out for all the courses of the Agricultural Sciences Centre (CCA/UFC) by the Educar Institute, which, in addition to these three aspects of the SINAES evaluation procedure, added the evaluation of the graduates, providing information on the need for greater adjustments in the curricular matrix to better reach the demands of society, especially those from Ceará State. Therefore, bibliographical, documentary and field research were carried out. On the bibliographic context, it was described the historical and institutional trajectory of higher education and evaluation policy in Brazil, as well as the generations of educational evaluation showing their characteristics and educational practices. In the documentary research, the Pedagogical Project of the Course of Agronomy (PPC), the Minutes of the CCA and Reports of MEC External Evaluations and of the Educar Institute were consulted. In the field research, qualitative data were obtained by means of semistructured interviews, performed with the Agronomy course coordinator and the formers ones, which occupied this position from 2008 a 2017. The results showed that SINAES evaluation procedure is positive, providing a better and deeply knowledge of the actual situation of graduation courses. The internal and external evaluations affected the PPC changings and, more specifically, the curricular matrix. Defining in a objective way their components, as supervised training, course finishing work, complementary activities and optional subjects offer, providing more flexibility, in order to respect the training areas of the PPC. The adjustments performed on the Agronomy course PPC has promoted benefits, with more students graduating and a significant improvement on the course evaluation score, obtained in 2017 after the visit of the MEC evaluators commission. Despite this, it still low the acceptance of evaluation processes by the academic community, including faculty and students, highlighting the need for a better announcement and awareness on the importance of evaluations, unliking from any kind of punishment, making them an important instrument to be used to get a better training of the future professionals. The use of SINAES evaluations information has contributed to improve the Agronomy course pedagogical Project, aiming to get a better undergraduate education quality and a more solid training of the future professionals.